IMPLEMENTASI PROGRAM GEMAS (GENERASI MENOLAK SAMPAH) SEBAGAI UPAYA PEMBENTUKAN BUDAYA SEKOLAH PEDULI LINGKUNGAN - Yunita Maharani; Wahyuni Wahyuni; Ummu Kalsum; Ahmad Nur; Nurul Aisyah; Arini Muhlisa; Aprisal Aprisal (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
Waste management problems in schools remain a challenge in fostering environmental awareness. The low level of students’ discipline in disposing and sorting waste encouraged the implementation of the GEMAS (Generasi Menolak Sampah) Program at SMPN 3 Majene as a community service initiative. This program aimed to develop positive habits and students’ responsibility toward waste management. A participatory method was applied by actively involving students in daily waste collection after school, waste sorting, cleaning, packaging, and weekly distribution to the School Waste Bank. The results indicated improved student discipline, better understanding of waste classification, and increased awareness of reducing single-use plastics. Overall, the GEMAS Program proved effective in establishing an environmentally conscious school culture and has the potential to be implemented as a sustainable waste management model in other educational institutions.